Real exchange rates and the J-Curve : evidence from Malaysia - Yusoff, Mohammed (Faculty Forum (USA), 2006)
The study aims at determining the effects of real bilateral exchange rate on Malaysia’s bilateral trade balance with its major trading partners: the USA, Japan, and Singapore. The results suggest that the bilateral trade balance, real exchange rate, domestic and foreign incomes are cointegrated. In the long-run, Malaysia’s bilateral trade balance is found to be responsive to the changes of bilateral exchange rates in the cases of the USA and Singapore but irresponsive for Japan. The short-run dynamic analysis indicates that there exist the J-curve effects in the cases of Malaysia’s trade balances with the USA, Japan and Singapore.